A novel and highly efficient Zr-containing catalyst based on humic acids for the conversion of biomass-derived ethyl levulinate into gamma-valerolactone. (1st April 2017) - Xiao, Zhenhuan; Zhou, Huacong; Hao, Jianmin; Hong, Hailong; Song, Yinmin; He, Runxia; Zhi, Keduan; Liu, Quansheng
Graphical abstract: Highlights: A novel MPV catalyst based on humic acids and Zr metal (HA-Zr) is prepared. HA-Zr is effective for MPV reaction with isopropanol as hydrogen source. Ethyl levulinate can be converted efficiently to γ-valerolactone by HA-Zr. Both performances and structures of HA-Zr are stable during reuse. Abstract: As the fast depletion of coal resources, exploring the value-added utilization approaches of low rank coals or their components and, in parallel, promoting the conversion of sustainable resources (such as biomass) into useful chemicals are critical issues facing human society. In this work, we used humic acids (HAs), an abundant material in nature (mainly derived from low rank coals), and the transition metal zirconium (Zr) to prepare a novel Zr-containing hydrogen transfer catalyst. The prepared catalyst was applied into the conversion of biomass-derived ethyl levulinate (EL) into gamma-valerolactone (GVL) via hydrogen transfer reaction. Both the preparation conditions of the catalysts and the reaction parameters during the conversion of EL into GVL were systematically investigated. The catalyst was characterized by SEM, TEM, FTIR, powder XRD, and TG analysis. The results demonstrated that the as-prepared catalyst was highly efficient for the conversion of EL into GVL. Under optimized conditions, EL could be completely converted and the GVL yield could reach up to 88.3%. The catalyst could be used at least 11 times without notable changes in both activity and structures, indicating an excellent stability. As far as we know, this is the first work using HAs to prepare Zr-containing catalyst and its application to the conversion of EL into GVL in biomass utilization.